TINGKAT PENGETAHUAN IBU HAMIL TENTANG ASI EKSKLUSIF BERDASARKAN KARAKTERISTIK DI PUSKESMAS PAYANGAN GIANYAR - Cokorda Istri Mita Pemayun; Lakitha Ning Utami; Sindi Maulindah (Journal of Midwifery and Health Administration Research, 2021)
Background: The low coverage of the success of exclusive breastfeeding in infants is influenced by many things, including the lack of knowledge and lack of information to mothers and families about the importance of exclusive breastfeeding. The purpose of this study was to describe the level of knowledge of pregnant women about exclusive breastfeeding at the Payangan Gianyar Health Center. Methods: The method of implementing this research is descriptive with a cross-sectional approach. The sample in this study were 38 pregnant women and were taken by accidental sampling. This research was conducted at the Payangan Gianyar Health Center in July 2021. The data processing used univariate analysis, namely descriptive. Results: from 38 respondents, it is known that most of them are 27-29 years old, as many as 11 respondents (28.9%); Most of the respondents' last education was SMA as many as 16 respondents (42.1%); most of the respondents as IRT as many as 20 respondents (52.6%); and most of the pregnant women who had their pregnancy checked at the Payangan Gianyar Health Center had good knowledge about the meaning of exclusive breastfeeding, as many as 28 respondents (73.7%) and as many as 10 respondents (26.3%) who had less knowledge about the meaning of exclusive breastfeeding. Conclusion: The results showed that most of the respondents had good knowledge about exclusive breastfeeding. Suggestion: the role of health workers who are very important in protecting, increasing, and supporting breastfeeding businesses as well as providers of health information are obliged to provide education. The form of these activities is that health workers, especially midwives, work together with health agencies to conduct counseling and counseling activities in order to increase mother's knowledge and information about the importance of exclusive breastfeeding.